Reasoning for whistleblowing in health care - Wiisak Johanna; Suhonen Riitta; Leino-Kilpi Helena (Wiley, 2022)
Background
Whistleblowing is recognised as part of solving wrongdoing. It requires individual reasoning as it is a potentially complicated process with a risk of possible negative consequences for oneself. Knowledge on how individuals reason for whistleblowing in healthcare context is lacking.
Aim
This study aimed to create a theoretical construct to describe individual reasoning for whistleblowing.
Methods
The methodology was grounded theory, with 244 nurses as informants. The data consisted of nurses' written narratives in response to a wrongdoing situation presented in a video vignette. To ensure the heterogeneity of the population and variation in nurses' professional expertise, experiences and geographical locations in health care to capture the multidimensionality of the responses, nurses were invited to participate, and data were collected electronically from the membership register of the Finnish Nurses' Association on a national level. Constant comparison was used to analyse the open data.
Results
The core category of the theoretical construct, 'The formation of morally courageous intervening', was discovered, reflecting individual's values and beliefs. It forms mentally as an integration of cognition and emotion for recognising one's own strengths and limits to act to do the right thing despite the risk of negative consequences for oneself. The core category consists of three dimensions of reasoning: (1) Reasoning Actors, (2) Reasoning Justifications and (3) Reasoning Activities, their categories and three patterns of reasoning connecting the dimensions and their categories with each other: (I) Individual Reasoning, (II) Collaborative Reasoning and (III) Collective Reasoning.
Discussion and conclusion
The theoretical construct indicate that reasoning is a multidimensional phenomenon. In future, a theoretical construct could be further developed. In health care, managers could use the theoretical construct to support employees in their whistleblowing.